Erosion thickness estimate and hydrocarbon accumulation period of relic basins: A case study of the Wulan‐Hua Sag in southern Erlian Basin, NE China. (26th July 2019) - Fu, Sheng; Liu, Zhen; Zhang, Yi‐ming; Jiang, Shuan‐qi; Wang, Xin; Wang, Hui‐lai; Tian, Ning; Yang, Hui‐li
Abstract : We conducted a study in the Wulan‐Hua Sag, a Mesozoic relic sag in the Erlian Basin to analyse and determine the period of its hydrocarbon accumulation. Estimation of erosional thickness is carried out from sonic well logs and seismic velocity data, followed by defining burial history of the Wulan‐Hua Sag together with thermal history through basin modelling. Fluid inclusions and pore fluid microthermometric data of 37 samples from clastic reservoir in the Wulan‐Hua Sag are available for detailed correlation and analysis. The reconstructed erosion thickness indicates that first of all, differential uplift that is characterized by seesaw uplift‐erosion initiated at the north sub‐sag. Secondly, largest erosion degree appears in Tumu'er and Saiwusu tectonic belts. Thirdly, the thickness of sedimentary rocks removed by erosion in the south sub‐sag progressively increases from its subsiding centre outwardly. Burial history of the Wulan‐Hua Sag belongs to type of late‐period intensive uplift‐erosion. Two types of fluid inclusion are recognized in the Wulan‐Hua Sag indicating two hydrocarbon accumulation periods for reservoirs in LK1 bt1 (lower interval in first member of Tengge'er Formation), which is middle depositing period of K1 bt1 (first member of Tengge'er Formation) to early depositing period of K1 bt2 (second member of Tengge'er Formation) and early K1 bt2 to middle K1 bs (Saihantala Formation) depositing period, respectively. Reservoir in the K1 ba and upper interval of K1 bt1 appears to have experienced one hydrocarbon accumulation period, which is early K1 bt1 to early K1 bt2 depositing period. And reservoir in the UK1 bt1 (upper interval in first member of Tengge'er Formation) also has one hydrocarbon accumulation period, which is late K1 bt2 depositing period to the Late Cretaceous (K2 ). Hydrocarbon accumulation model of the Wulan‐Hua Sag consists of two oil‐reservoir types including "upward‐charging" and "self‐sourced." Reservoir in lower interval of K1 bt1 and reservoir in the upper interval of K1 bt1 are considered to have more hydrocarbon exploration potential.